The dynamic relationship between house prices and output: evidence from US metropolitan areas - Apergis, Nicholas; Simo-Kengne, Beatrice D.; Gupta, Rangan; Chang, Tsangyao (International Journal of Strategic Property Management, 2015)
This paper investigates the long-run and short-term dynamics of 351 US metropolitan statistical area housing prices in relation to personal income. We apply a panel cointegration approach on annual data from 1993 to 2011 and find a long-run relationship between local house prices and per capita personal income. The causal direction is then assessed based on an autoregressive distributed lag specification that also accommodates for error-correction. Results from Granger-causality tests reveal the existence of a bi-directional causality between real house prices and real per capita personal income over both long and short-horizons. Our results continue to be robust, when our bivariate system is extended to include additional MSA-level (employment and population) and national-level variables (real stock price and mortgage interest rate). We conclude that changes in personal income can predict house price movements and vice versa.First Publish Online: 23 Dec 2015